V bran izraznemu pojmovanju pravil - Kristan, Andrej (Revus (Ljubljana), 2014)
Against a background of the past three decades of critique directed towards the expressive conception of norms, the author argues first that paradigm expressivists can well account for facultative states of affairs without introducing inconsistencies into the normative system. He then shows how to describe the propositional content of a meta-rule without semanticizing the force indicator of object-rules. Finally, the author provides a formal reconstruction of conditional norms and of permissive closure, without admitting the conceptual autonomy of acts of permitting. The first parts of this paper are of a clarifying nature, whereas the last parts purport to present an advancement in the expressivist theory.
Keywords: dovolilna zapora; logična teorija normativnih sistemov; metapravila; pogojna pravila; prednostna pravila